Pendampingan Pekerjaan Perbaikan Pondasi Gedung Raja Manguntu Untuk Pengembangan Desa Wisata Di Desa Lapandewa Kec. Lapandewa Kab. Buton Selatan - Musrifin Musrifin; Muhammad Chaiddir Hajia; La Farji; Angga Setiawan (IAIN AMBON, 2022)
One way to increase people's income is through tourism development that utilizes local resources. Many regions in Indonesia are competing to manage their natural resources and package them as tourism products, one of which is the Raja Maruntu Building which is a favorite gathering place for the people of Lapandewa Village where the condition of the foundation of this building needs improvement. When there are tourist attractions in the vicinity, the community's creative economy becomes more alive. What we mean is that tourism is a means to boost the economy. Therefore, academic intervention is important to ensure that the community is able and willing to develop and manage local resources into tourism objects that are able to raise the standard of living of the community. The implementation method is that the mentoring team invites the Lapandewa Village Government. This event will be held in conjunction with the implementation of a comprehensive program. After that, a discussion or question and answer session will be held. After the discussion session is over, the next task is to set a schedule for submitting permits to stakeholders in Lapandewa Village. By participating in this service, the Lapandewa Village Government hopes to cooperate with the UM Buton Faculty of Engineering in socialization and training activities that aim to improve the performance of the Lapandewa Village GovernmentKeywords: Tourism Village, Lapandewa Village, Foundation